Membangun Budaya Anti Gratifikasi di Desa Cendana Kab. Enrekang - Aris, Ardiyanti; Syahril, Muh. Akbar Fhad (Amsir Community Service Journal, 2025)
One form of corruption that is not realized by the community is the act of gratification. Efforts that can be made to prevent gratification are one of which is by increasing socialization or legal counseling to the community. Legal counseling is given as a concept of community service to provide an understanding of the importance of Anti-Gratification Culture for the Cendana Village Community. Increasing the awareness of the Cendana Village Community about the Importance of Anti-Gratification Culture, it is hoped that they will be able to participate in supervision and not tolerate any form of gratification as a form of gratitude.